Measurement of sigma(p(p)over-bar -> Z)center dot Br(Z ->tau tau) at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Soc, 2005)
We present a measurement of the cross section for Z production times the branching fraction to tau leptons, sigma.Br(Z ->tau(+)tau(-)), in p (p) over bar collisions at root s=1.96 TeV in the channel in which one tau decays into mu nu(mu)nu(tau), and the other into hadrons+nu(tau) or e nu(e)nu(tau). The data sample corresponds to an integrated luminosity of 226 pb(-1) collected with the D0 detector at the Fermilab Tevatron collider. The final sample contains 2008 candidate events with an estimated background of 55%. From this we obtain sigma.Br(Z ->tau(+)tau(-)) = 237 +/- 15(stat)+/- 18(sys)+/- 15(lum)pb, in agreement with the standard model prediction.